ANALYSIS OF EFFECTS OF RECEIVABLE TURNOVER AND INVENTORY TURNOVER ON PROFITABILITY OF MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED IN THE INDONESIA STOCK EXCHANGE (ISE) FOR PERIOD OF 2015-2017 - Yanti; Apriani Sujaya, Fista; Fadjar, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to determine the receivable turnover rate and inventory turnover have an influence on profitability both partially and simultaneously in a company. The object of this research is a consumer goods industry sector manufacturing company that listed on Indonesia Stock Exchange in the period 2015-2017. The type of data in this research is quantitative data. The source of the data in this research is secondary data, in the form of financial report data (balance sheet and income statement) related to variable in this research. The results of this research indicate that Receivable Turnover has an effect on profitability. While inventory turnover does not affect on profitability. The results of the research simultaneously indicate that Receivable Turnover and inventory turnover influence together on profitability.